2021
DOI: 10.4018/ijea.2021010104
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, Personality Traits, and the Use of Facebook

Abstract: Different personality traits respond differently to unfavourable life situations. Unemployment can have several negative social, economic, and domestic consequences. Many people use social media for a variety of reasons. The aim of this study is to examine the way different personality traits respond to Facebook in the period of unemployment. Data was obtained from 3,002 unemployed respondents in Nigeria. The study used regression model to analyse the data. Among the five personality traits, results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A study to learn more about their characteristics was undertaken (Törőcsik et al, 2014). A research revealed that a favourable association between conscientiousness and online social support was discovered on the social websites platform (Ukpabi et al, 2021).The research revealed both post-millennials and millennials are tech experts and seek and distribute information globally with great ease (Berkup, 2014). Post-Millennials and Millennials readily adapt and leverage the advanced technology for communication irrespective of which generation they belong to (Levickaite, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study to learn more about their characteristics was undertaken (Törőcsik et al, 2014). A research revealed that a favourable association between conscientiousness and online social support was discovered on the social websites platform (Ukpabi et al, 2021).The research revealed both post-millennials and millennials are tech experts and seek and distribute information globally with great ease (Berkup, 2014). Post-Millennials and Millennials readily adapt and leverage the advanced technology for communication irrespective of which generation they belong to (Levickaite, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Millennial and Social Websites: Research conducted (Ukpabi et al, 2021) revealed that employees in younger and older age groups have different levels of acceptance of certain technological factors. Businesses may use these distinctions to plan effective social website campaigns and create branding plans that are appropriate for various generation (Vasudeva, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%